2014
DOI: 10.1186/1743-422x-11-46
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis of a frog virus 3 (FV3) isolate and sequence comparison with isolates of differing levels of virulence

Abstract: BackgroundFrog virus 3 (FV3) is the type species of the genus Ranavirus, and in the past few decades, FV3 infections have resulted in considerable morbidity and mortality in a range of wild and cultivated amphibian species in the Americas, Europe, and Asia. The reasons for the pathogenicity of FV3 are not well understood.FindingsWe investigated three FV3 isolates designated SSME, wt-FV3, and aza-Cr, and reported that our wt-FV3 and aza-Cr strains showed similar levels of virulence, while SSME was the least vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
0
34
0
3
Order By: Relevance
“…Frog virus 3 infection results in considerable morbidity and mortality in a wide range of wild and cultivated amphibian species [32][33][34][35].…”
Section: Ranaviruses and Their Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frog virus 3 infection results in considerable morbidity and mortality in a wide range of wild and cultivated amphibian species [32][33][34][35].…”
Section: Ranaviruses and Their Genomesmentioning
confidence: 99%
“…The genomes of two LCDVs, LCDV-1 and LCDV-C have been completely sequenced. LCDV-1, which infects plaice and flounder, was isolated from the propagated cell lines of bluegill and centrarchid fish in 1966 [32][33][34][35] and had its genome completely sequenced in 1997 [22]. LCDV-C was originally iso- [23,43,57].…”
Section: Lcdv Genomesmentioning
confidence: 99%
“…Perhaps viral replication was favored at 15 °C more than the host's immune system, whereas the immune system was dominant at 20 °C . Similarly, Echaubard et al ( 2014 ) found that the rate of mortality in experimental epidemics with northern leopard frog and wood frog tadpoles was greater at 14 °C than at 22 °C in control populations and those exposed to two FV3-like ranaviruses, providing additional evidence that temperature can infl uence ranavirus epidemics, but likely depends on the host and type of virus (Echaubard et al 2014 ). In conclusion, there are likely multiple mechanisms through which temperatures can infl uence ranavirus infections.…”
Section: Temperature and Susceptibilitymentioning
confidence: 97%
“…In addition to coding regions, ranavirus genomes contain palindromes, microsatellites, repeat regions, and areas of inter-and intragenic variation (Eaton et al 2010 ;Jancovich et al 2003 ;Lei et al 2012b ;Mavian et al 2012 ;Morrison et al 2014 ;Tan et al 2004 ). Repeat and variable regions may serve as sites that facilitate recombination or regulate gene expression, and palindromic sequences at the 3′ end of viral messages may act as transcriptional termination signals.…”
Section: Ranavirus Taxonomy and Genomesmentioning
confidence: 99%
“…Repeat and variable regions may serve as sites that facilitate recombination or regulate gene expression, and palindromic sequences at the 3′ end of viral messages may act as transcriptional termination signals. In addition, comparisons of closely related FV3-like viruses that vary in virulence suggest that intragenic differences, as well as variation within repeated sequences, may infl uence viral pathogenesis (Morrison et al 2014 ).…”
Section: Ranavirus Taxonomy and Genomesmentioning
confidence: 99%